2017
DOI: 10.1038/s41598-017-01914-x
|View full text |Cite
|
Sign up to set email alerts
|

In situ printing of mesenchymal stromal cells, by laser-assisted bioprinting, for in vivo bone regeneration applications

Abstract: Bioprinting has emerged as a novel technological approach with the potential to address unsolved questions in the field of tissue engineering. We have recently shown that Laser Assisted Bioprinting (LAB), due to its unprecedented cell printing resolution and precision, is an attractive tool for the in situ printing of a bone substitute. Here, we show that LAB can be used for the in situ printing of mesenchymal stromal cells, associated with collagen and nano-hydroxyapatite, in order to favor bone regeneration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
242
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(267 citation statements)
references
References 37 publications
1
242
0
6
Order By: Relevance
“…The results showed that cellular arrangements had obvious impacts on bone tissue regeneration ( Fig. 2b) [49]. Fedorovich et al printed intricate porous constructs containing endothelial progenitors and multipotent stromal cells embedded within Matrigel and alginate [50].…”
Section: Bioprinting Of Bonementioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that cellular arrangements had obvious impacts on bone tissue regeneration ( Fig. 2b) [49]. Fedorovich et al printed intricate porous constructs containing endothelial progenitors and multipotent stromal cells embedded within Matrigel and alginate [50].…”
Section: Bioprinting Of Bonementioning
confidence: 99%
“…2a that hMSCs differentiated into perivascular cells in co-culture with HUVECs at day 7, forming a stabilized vasculature in the bone-like construct [48]. Based on the in vitro researches of 3D bioprinting for tissue engineering, Keriquel et al in situ printed MSCs-laden nano-hydroxyapatite and collagen bioinks in calvaria defec- Reproduced with permission [49]. Open Access tive mice.…”
Section: Bioprinting Of Bonementioning
confidence: 99%
“…In laser‐assisted printing, a ribbon in glass or quartz is coated by a thin layer of metal (i.e., gold, titanium), which is then loaded with the bioink. A laser pulse induces the vaporization of the metal film resulting in the formation of a high pressure bubble that pushes a droplet of bioink toward the substrate . Laser‐assisted printing requires the use of bioinks with viscosities (<300 mPa s).…”
Section: Skeletal Muscle Tissue Engineeringmentioning
confidence: 99%
“…Bioprinting technologies can also be adapted to do in situ bioprinting. A recent example showed a laser-assisted bioprinting for in situ bioprinting of mesenchymal stromal cells in collagen and hydroxyapatite for bone tissue regeneration [16]. In situ bioprinting would be helpful for computerassisted medical interventions and development of medical bio-robotics.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%